A Novel Method for the Synthesis of Indolo[2,1-a]isoquinolines - Lotter, Angelique Natalia Cassandra (My University, 2006)
Many azapolycyclic aromatic ring systems, whether they are naturally occurring or synthetically made, display important biological activities. One important class of naturally occurring azapolycyclic aromatic ring systems are the dibenzopyrrocoline alkaloids, which contain an indole ring fused to an isoquinoline moiety, where they share a common nitrogen. The basic skeleton of these alkaloids is the indolo[2,1-a]isoquinoline nucleus. Both the dibenzopyrrocoline alkaloids and the indolo[2,1-a]isoquinolines have been found to inhibit tubulin polymerization and thus possess antitumour and antileukemic activities. In our laboratories, a variety of indolo[2,1-a]isoquinolines, for example 5,12- dimethyl-6-phenylindolo[2,1-a]isoquinoline, have been synthesized using the Suzuki-Miyaura cross coupling reaction and reaction conditions for the formation of aromatic rings (KOBut in DMF and a light source – developed in our laboratories) as key steps. In this dissertation we discuss the synthesis of (±)-5,6-dihydro-6-phenylindolo[2,1-a]isoquinolin-5-ol and ethyl indolo[2,1- a]isoquinoline-6-carboxylate using these reaction conditions as our key steps. The syntheses commenced with the N-protection of isatin with a benzyl and an ethyl acetate group to afford 1-benzylindoline-2,3-dione and ethyl 2-(2,3- dioxoindolin-1-yl)acetate respectively. The next step was the synthesis of the brominated compounds 1-benzyl-2-bromo-1H-indole and ethyl 2-(2-bromo- 1H-indol-1-yl)acetate by means of a functional group interconversion of the oxygen in the 3-position to two chlorine atoms, followed by hydrodehalogenation, using zinc in AcOH, and then bromination, using POBr3 in CH2Cl2. Having obtained the brominated compounds we went on and coupled them with 2-formylphenylboronic acid using the Suzuki-Miyaura cross coupling reaction to obtain the coupled products 2-(1-benzyl-1H-indol-2- yl)benzaldehyde and ethyl 2-(2-(2-formylphenyl)-1H-indol-1-yl)acetate in 92 and 77% yield, respectively. Aromatisation of ethyl 2-(2-(2-formylphenyl)-1Hindol- 1-yl)acetate to ethyl indolo[2,1-a]isoquinoline-6-carboxylate occurred smoothly in 2 minutes using 10 mol % KOBut in DMF at room temperature. Using the same reaction conditions on 2-(1-benzyl-1H-indol-2- yl)benzaldehyde to form 6-phenylindolo-[2,1-a]isoquino-line resulted in (±)- 5,6-dihydro-6-phenylindolo[2,1-a]iso-quinolin-5-ol being obtained in 75% yield (7:3 ratio of anti:syn). An attempt to dehydrate this compound using p-TSA in CH2Cl2 in the presence of molecular sieves was not successful. Time constraints prevented any further attempts at dehydrating (±)-5,6-dihydro-6- phenylindolo[2,1-a]iso-quinolin-5-ol. In conclusion, we managed to synthesize (±)-5,6-dihydro-6-phenylindolo[2,1- a]isoquinolin-5-ol and ethyl indolo[2,1-a]isoquinoline-6-carboxylate using the Suzuki-Miyaura cross coupling reaction and specific reaction conditions, using the base KOtBu, for the formation of aromatic rings, both as key steps.
MSc dissertation School of Chemistry Faculty of Science 0004984F
Keywords: Indolo[2,1-a]isoquinolines; 5,6-dihydro-6-phenyl[2,1-a]isoquinolin-5-ol; ethyl indolo[2,1-a]isoquinoline-6-carboxylate; Suzuki-Miyaura cross coupling reaction